Analysing the experiences of casual relief teachers in Australian primary schools using practice architecture theory. (2nd June 2020) - Uchida, Minami; Cavanagh, Michael; Lane, Rod
Abstract : This study examines the professional experiences of casual relief teachers (CRTs) and some of the challenges they face through the lens of practice architecture theory. Practice architecture theory considers human activity through the multi‐layered lens of sayings, doings and relatings. A survey was used to collect responses from 104 CRTs who are teaching or have previously taught in Australian primary schools. The responses were examined using thematic content analysis to gain insights into their experiences of professional practice. In addition, the demographic information from the survey identified three main categories of CRTs which contributed to better understanding of distinct needs and experiences of each type of CRT. Results indicate that many participants saw casual teaching as a negative and alienating experience due to lack of access to school information, lack of support for accreditation and feelings of exclusion from school communities. The need for greater access to information about professional learning was also highlighted. However, others enjoyed the flexibility and sense of belonging they experienced as CRTs. The present study contributes to CRT research by identifying similarities and differences across the three CRT groups and applying practice architectures as a new theoretical lens through which to analyse their professional experiences.